A história da matemática como recurso didático para o ensino e a aprendizagem de conceitos geométricos - Schmidt, Giovani Marcelo (2014)
This research sought to investigate the pedagogical potential of using the history of mathematics in the classroom to assist in the teaching and learning of Mathematics process instrument. The study aimed to the teaching learning geometry using the history of mathematics and problem solving in building concepts for understanding the theorem of Thales. From the literature review and comment on the use of history of mathematics as a pedagogical resource, outlined this search hypothesizing that it should be associated with the teaching and learning of mathematics process. Thus, considering the importance of this area in the process, formulated the following research problem: the History of Mathematics can become didactic resource for teaching and learning of geometric concepts? Were applied activities in a class of eighth graders at a public school in the city of Santa Maria, Rio Grande do Sul, where the history of mathematics served as guideline for understanding the theorem of Thales. Also treated in the context of the study of mathematics and Troubleshooting, pointing out some positive and negative aspects regarding the use of history of mathematics and its relevance in the classroom or not. Attention was points where it can be used in the development and implementation of activities aimed at building the basics of geometric concepts, allowing students could perceive the investigative character in this generation, organization and dissemination of these concepts throughout its historical development. The research was developed whether through five activities being the first one Pre Test to verify the previous knowledge of the students in Geometry and other leading learners to be able to resolve the initial question. Data were collected through the delivery of the activities and a daily class in which the teacher researcher made notes of situations not represented in the activities delivered.